2007
DOI: 10.1111/j.1469-7610.2007.01812.x
|View full text |Cite
|
Sign up to set email alerts
|

What do childhood anxiety disorders predict?

Abstract: Anxiety disorders in childhood are predictors of a range of psychiatric disorders in adolescence. It appears that children meriting a well-defined diagnosis are missed by the current rules for the diagnosis of GAD. Future studies should examine whether OAD deserves reconsideration as a nosological entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
366
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 620 publications
(384 citation statements)
references
References 40 publications
12
366
0
6
Order By: Relevance
“…3 Several randomized controlled trials 4 have demonstrated that 50% to 70% of children with anxiety disorders are free of their primary anxiety diagnosis after cognitive-behavioral therapy (CBT). 5 A substantial minority of children with anxiety disorders, however, does not show a clinically significant improvement after CBT.…”
mentioning
confidence: 99%
“…3 Several randomized controlled trials 4 have demonstrated that 50% to 70% of children with anxiety disorders are free of their primary anxiety diagnosis after cognitive-behavioral therapy (CBT). 5 A substantial minority of children with anxiety disorders, however, does not show a clinically significant improvement after CBT.…”
mentioning
confidence: 99%
“…Associations of lower selfefficacy with anxiety symptoms and disorders have been shown in several studies [22,23]. Thus, we expected a reduced sense of personal control in young children to constitute a mediator between a negative restrictive family environment, parents` worrying and subsequent negative affect and anxiety symptoms [24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Predictor Variablesmentioning
confidence: 97%
“…Most studies on the significance of these variables for the manifestation of anxiety had some weaknesses regarding limitations in the operationalization of constructs, their cross-sectional study design or retrospectively assessed data [34,37]. The current study included therefore parental worrying and dysfunctional parenting, in the sense of restrictive behavior as well as reproach and inconsistent behavior and the latter assessed as perceived and recalled behavior of the parents estimated by the child.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…The 12-month prevalence of agoraphobia is approximately 1.7% in adolescents and adults (Kessler et al, 2012;Wittchen et al, 2011). Onset of agoraphobia can occur during childhood but the most vulnerable periods to develop the disorder are late adolescence and early adulthood (Beesdo et al, 2009;Bittner et al, 2007). The gender ratio is 2:1 with females experiencing twice as often agoraphobia as men .…”
Section: Prevalencementioning
confidence: 99%